KEMAMPUAN PEMECAHAN MASALAH DITINJAU DARI INTELLIGENCE QUOTIENT (IQ) PADA PEMBELAJARAN BERBASIS GAMES BERBANTUAN MATH MASTER - Hesti Yunitiara Rizqi; Lisa Virdinarti Putra (Jurnal Educhild : Pendidikan dan Sosial, 2023)
The low problem-solving ability of students is a current problem because of the importance of problem-solving ability which is the most basic ability of students in solving math problems. This study aims to see the effectiveness of math master-assisted games-based mathematics learning, to describe and analyze students' problem-solving abilities in terms of intelligence quotient (IQ). This study used a mixed methods research with a sequential explanatory design. The research subjects were students of class VI at SDN 04 Susukan, Semarang Regency. The instruments used is of problem-solving ability tests and observation sheets. The results of the study showed (1) The students' mathematical problem solving abilities in the high IQ category could fulfill all indicators of mathematical problem solving, namely from the test answer sheets they could understand the problem until they checked the results again. Students with normal IQ can understand the problem until they can implement a plan to solve the problem. Students with low or below normal IQ, they cannot meet all the indicators but they can understand the problem and can make a problem solving plan from the questions (2) learning games based mathematics assisted by math master is very effective, and it can be seen from the number of students with mathematical problem solving skills in the achievement of medium, good, and very good categories the number is more than students who are still in the low category. This means that math master-assisted games-based learning is effective and can develop students' mathematical problem-solving skills.Rendahnya kemampuan pemecahan masalah siswa menjadi permasalahan saat ini karena pentingnya kemampuan pemecahan masalah menjadi kemampuan paling mendasar siswa dalam menyelesaikan masalah matematika. Penelitian ini bertujuan untuk melihat keefektifan pembelajaran matematika berbasis games berbantuan math master, mendeskripsikan dan menganalisis kemampuan pemecahan masalah siswa ditinjau dari IQ. Penelitian ini menggunakan penelitian mix methods dengan sequential explanatory design. Subjek penelitian adalah siswa kelas VI SDN 04 Susukan, Kabupaten Semarang. Instrumen yang digunakan adalah tes kemampuan pemecahan masalah dan lembar observasi. Hasil penelitian menunjukkan (1) Kemampuan pemecahan masalah matematika siswa pada kategori IQ tinggi dapat memenuhi semua indikator pemecahan masalah matematika, yaitu dari lembar jawaban tes mereka dapat memahami masalah sampai mengecek kembali hasil yang didapat. Siswa dengan IQ normal dapat memahami masalah sampai dengan dapat melaksanakan rencana dalam memecahkan masalah. Siswa dengan IQ rendah atau dibawah normal, mereka tidak dapat memenuhi semua indikator namun mereka dapat memahami masalah dan dapat membuat rencana pemecahan masalah dari soal (2) Pembelajaran matematika berbasis games berbantuan math master sangat efektif, dan terlihat dari jumlah siswa dengan kemampuan pemecahan masalah matematika pada pencapaian kategori sedang, baik, dan sangat baik jumlahnya lebih banyak dari pada siswa yang masih dalam kategori rendah. Dengan demikian berarti bahwa pembelajaran matematika berbasis games berbantuan math master efektif dan dapat mengembangkan kemampuan pemecahan masalah matematika siswa.